SISTEM INFORMASI GEOGRAFIS PERSEBARAN SEKOLAH KESETARAAN SEBAGAI ALTERNATIF ANAK PUTUS SEKOLAH DI KABUPATEN DEMAK - Hanun Ravi Putra Wardana; Bambang Agus Herlambang; Ahmad Khoirul Anam (CV. ADIBA AISHA AMIRA, 2024)
One of the important components in the development of society is education. But kids are still dropping out of school in many places, including in Demak District. Therefore, innovative solutions are needed to address this problem. The aim of this research is to create a geographical information system (GIS) that can map and analyze how equality schools are spread across Demak district as an educational alternative for school dropouts. The waterfall method used with the Quantum GIS software used in this study aims to provide an accurate picture of the educational status and distribution of equality schools in Demak District. Buddhism is used as a reference in the data collection process. Therefore, this study can provide a thorough analysis of the difficulties and opportunities that exist to address the problem of school dropout in the region. Besides, this research can provide a strong foundation for creating better educational solutions.